Prudential and oversight requirements for securities settlement - Daniela Russo; Giacomo Caviglia; Chryssa Papathanassiou; Simonetta Rosati (European Central Bank (ECB), 2007)
This paper is analysing the current national and international regulatory regimes relevant for European banks, CSDs and ICSDs, and is comparing them with the requirements in order to answer the following questions - Is there any overlap between the provisions of the CPSS-IOSCO Recommendations and the existing international and national requirements to which European SSSs and banks are subject? Are current provisions equivalent or more restrictive (“super-equivalent”) for banks and CSDs? In what respect? Does the overlap between the CPSS-IOSCO Recommendations and existing regulation result in double requirements?.
Keywords: 330; Wertpapierhandel; Bankenaufsicht; Finanzmarktaufsicht; EU-Staaten